Hemodynamics and Bleb Formation in Intracranial Aneurysms - Cebral, J.R. (American Society of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: Intracranial aneurysms with irregular shapes and blebs or secondary outpouchings have been correlated with increased rupture risk. The purpose of this study was to investigate possible associations between the local hemodynamics and the formation of blebs in cerebral aneurysms. MATERIALS AND METHODS: Computational models of 20 cerebral aneurysms harboring 30 well-defined blebs were constructed from 3D rotational angiographies. Models representing the aneurysm before bleb formation were constructed by virtually removing the blebs from the anatomic models. Computational fluid dynamics simulations of the aneurysm before and after bleb formation were performed under pulsatile flows. Flow and WSS visualizations were used to analyze the local hemodynamics in the region of the aneurysm that developed the bleb. RESULTS: Most blebs (80%) occurred at or adjacent to the aneurysm region with the highest WSS before bleb formation, and near the flow impaction zone. Most blebs (83%) were found in regions of the aneurysm previously subjected to high or moderate WSS and progressed to low WSS states after the blebs were formed. Most blebs (77%) were aligned or adjacent to the inflow jet, whereas 17% were aligned with the outflow jet, and only 6% were not aligned with the flow direction. In addition, 90% of the aneurysms had maximal WSS higher than or similar to the WSS in the parent artery. CONCLUSIONS: Blebs form at or adjacent to regions of high WSS and are aligned with major intra-aneurysmal flow structures. Formation of blebs results in a lower WSS state with formation of a counter current vortex. These findings imply that locally elevated WSS could contribute to the focalized wall damage that formed these structures.